2020
DOI: 10.1111/jcal.12473
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing learning without sacrificing the fun: Stealth assessment, adaptivity and learning supports in educational games

Abstract: In this study, we investigated the validity of a stealth assessment of physics understanding in an educational game, as well as the effectiveness of different game-level delivery methods and various in-game supports on learning. Using a game called Physics Playground, we randomly assigned 263 ninth-to eleventh-grade students into four groups: adaptive, linear, free choice and no-treatment control. Each condition had access to the same in-game learning supports during gameplay. Results showed that: (a) the stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 46 publications
(74 reference statements)
2
41
0
Order By: Relevance
“…Instructive games have been utilized to show content in different subjects, for example, science [21], arithmetic, and physical science [22], just as exploration on natural frameworks [23]. what's more, have been displayed to study and further foster understudies' non-scholarly capacities like innovativeness (e,g, Blanco-Herrera, Gentile, and Rokkum, Shute and Rahimi), and eager (e,g, Blanco-Herrera, Gentile, and Rokkum) [24][25]. These and other tests are considered positive, but further exploration is needed.…”
Section: Resultsmentioning
confidence: 99%
“…Instructive games have been utilized to show content in different subjects, for example, science [21], arithmetic, and physical science [22], just as exploration on natural frameworks [23]. what's more, have been displayed to study and further foster understudies' non-scholarly capacities like innovativeness (e,g, Blanco-Herrera, Gentile, and Rokkum, Shute and Rahimi), and eager (e,g, Blanco-Herrera, Gentile, and Rokkum) [24][25]. These and other tests are considered positive, but further exploration is needed.…”
Section: Resultsmentioning
confidence: 99%
“…But, without doubt, educational games should be designed appropriately for the “high explorer” type of student. There is a way to embedded assessments in educational games that does not knock the joy out of a game (Shute et al, 2020), and students must also have time to explore and push on the edges of a game. But at some point, the in‐process data being collected needs to be a sensitive (valid and reliable) measurement of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…For example, these can be embedded puzzles or game‐like tasks to assess learning during play (Johnson‐Glenberg et al, 2015; Shute, 2011). Shute et al (2020) report their in‐game stealth assessments were significantly correlated with external, post‐play physics test scores. It has been argued that in‐game assessments can alleviate the necessity of using external evaluations (Plass et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the theoretically expected learning gains, the literature on the effectiveness of adaptive game‐based learning presents mixed results. Some studies reported increased learning outcomes due to adaptivity (Sampayo‐Vargat et al, 2013, Sandberg, et al, 2014), while others did not find similar effects (Shute et al, 2020; Vanbecelaere et al, 2020b; Van Klaveren et al, 2017). A recent meta‐analysis including 12 studies comparing adaptive with non‐adaptive practice, did not produce a substantial overall effect when combining effects on learning outcomes, game performance and engagement (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%